EFEKTIVITAS MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN STML PADA PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA - Nasya, Alna; Subagiyo, Lambang; Qadar, Riskan (Jurnal Pendidikan Fisika FKIP UM Metro, 2025)
The low critical thinking ability of students is a concern of the education system for the success of learning in the 21st century. The combination of models with the right approach during learning is certainly needed to improve critical thinking skills.The solution to improve critical thinking skills is to apply a problem-based learning model with the SETS approach. This study used a pre-experiment method with a one group pretest-posttest design. The sample used amounted to 40 people who were taken with purposive sampling technique. This research instrument consists of essay questions that contain five indicators of critical thinking: a) provide simple explanations, b) build basic skills, c) conclude, d) provide further explanation, e)organize strategies and techniques. The results showed that the use of problem-based learning model with STML approach was effective in improving students' critical thinking skills. The most improved aspect is in the aspect of buildingbasic skills with an average N-Gain score of 0.80, and the least improved aspect is in the aspect of providing further explanation with an average NGain score of 0.52. These results can provide alternative ways to improve students' critical thinking skills through the application of innovative and cooperative learning models such as problem-based learning with the SETS approach